2023
DOI: 10.1007/s12155-023-10595-6
|View full text |Cite|
|
Sign up to set email alerts
|

Design of Experiments Study on Scottish Wood Biochars and Process Parameter Influence on Final Biochar Characteristics

Abstract: Native Scottish wood samples were investigated as potential, locally sourced, raw materials for biochar production. Screening experiments identified pure softwood as the preferable feedstock. Influence of operational parameters, i.e. activating gas flow rate (CO2), heating ramp rate and contact time on final biochar characteristics, was investigated using design of experiments. Surface area and biochar yield were selected as response variables. Minitab was used to define experimental run conditions and suggest… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…The aromatization process begins at approximately 350 °C and continues at higher temperatures [ 40 , 49 ]. The aromatic C–H deformation increased until the temperature reached 500 °C [ 43 ]. Amorphous carbons, the main biochar component, are structured as aromatic rings, giving biochar its characteristic stability [ 26 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The aromatization process begins at approximately 350 °C and continues at higher temperatures [ 40 , 49 ]. The aromatic C–H deformation increased until the temperature reached 500 °C [ 43 ]. Amorphous carbons, the main biochar component, are structured as aromatic rings, giving biochar its characteristic stability [ 26 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The atomic ratio of H/C decreases substantially as the pyrolysis temperatures rise, indicating that depolymerization procedures are occurring, which implies increased oxidation resistance [ 3 , 10 ]. In biochar with an atomic H/C ratio lower than 0.7, this indicates the experience of the aromatization processes mainly at pyrolysis temperatures greater than 400 °C [ 13 , 16 , 27 ]; it has better fused aromatic ring structures [ 43 , 58 ], making it highly stable and resistant in the soil ecosystem [ 1 , 19 , 39 ]. Accordingly, the results found that pyrolysis of DBC feedstock at a temperature ≥450 °C provided DBC biochar which had a high degree of aromaticity with an atomic ratio of H/C lower than 0.7.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been widely observed that biochar can be produced from many types of lignocellulosic biomasses, such as rice husk [27], wheat straw [28], shell and peel [29], herbaceous [30], tree branches and bark [31], paper sludge [32], and manure [33,34]. Recently, researchers have given considerable attention to wood-based feedstocks due to their abundant availability and favorable characteristics [25,35,36], especially wood wastes, which generate and drive a circular economy. Single-use or disposable bamboo chopsticks (DBCs) constitute a large proportion of urban waste worldwide because they are used for food consumption in Asian cultures.…”
Section: Introductionmentioning
confidence: 99%